Administrative Analysis of the Evaluation of Satisfaction of BPJS Kesehatan Contribution Assistance Recipients on the Quality of Health Insurance Services in Makassar City - Syarif, Kurnia Ali (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
The BPJS Kesehatan Contribution Assistance Recipient Program (PBI) is a form of the government's commitment to ensuring access to health services for the underprivileged and low-income communities. As part of the National Health Insurance (JKN) system, participants receiving assistance are entitled to receive free health services at facilities in collaboration with BPJS. However, in the midst of efforts to equalize services, complaints were still found related to service quality, such as irregular queues, limited medicines, and discriminatory treatment. This study aims to evaluate the level of satisfaction of recipients of assistance with the quality of health services in the city of Makassar, focusing on aspects of the friendliness of health workers, the use of BPJS cards, the efficiency of the service process, and the accessibility of health facilities. Using a qualitative approach with descriptive-analytical methods and analysis of the dimensions of service quality, the results showed that most participants were satisfied with the services received, especially in terms of equal treatment and smooth administrative processes. These findings indicate that digitalization and bureaucratic reform are starting to have a positive impact, although equitable distribution of service quality across regions is still a challenge. This research is expected to make an academic contribution to the development of public service evaluation studies as well as practical recommendations for BPJS kesehatan and local governments in improving the quality of inclusive and equitable health services